Determinan Fraudulent Financial Statement: Peran Komite Audit Sebagai Pemoderasi - Alkotdriyah, Putri Puspa; Harnovinsah, Harnovinsah; Djaddang, Syahril; Mulyadi, JMV; Lysandra, Shanti (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2024)
The phenomenon of Fraudulent Financial Statement contributes the largest average loss in the world compared to other types of fraud and the involvement of property and real estate sector companies in Fraudulent Financial Statement scandal prompts researchers to investigate further regarding this phenomenon. With regard to the impact of the fraud pentagon on fraudulent financial statements, this study attempts to provide empirical proof of moderating role of audit committee in Property and Real Estate companies for the period 2020-2022 with an observed sample size of 54 companies. Purposive sampling was the sample technique chosen for the present inquiry. IBM SPSS Statistics 26 used to scrutinize the gathered data by means of moderated regression analysis technique. It was discovered that Fraudulent Financial Statements have proved to be significantly impacted by Financial Stability and Total Accruals. Meanwhile, moderating effect provided results that from the abundance of five Pentagon Fraud indicators, only Financial Stability can be significantly moderated by the audit committee.